Current trends in the treatment of recurrent adenocystic cancer of the salivary glands: case report - O. A. Saprina; M. A. Kropotov; S. A. Tulyandin; K. A. Ganina; N. A. Kozlov; B. B. Vizigina (Опухоли головы и шеи)
Salivary gland carcinomas is a rare family of neoplasms with different histological characteristics and biological behavior. Treatment regimens have remained virtually unchanged for decades, leaving the leading role for surgical treatment and radiation therapy. However, a special place in the salivary gland carcinomas group is occupied by adenoid cystic carcinoma, which is quite often characterized by a recurrent and / or metastatic course with the use of chemotherapy as the main option in treatment. It is worth noting the fact that the results of standard chemotherapy regimens show unsatisfactory results, respectively, with recurrent or metastatic adenoid cystic carcinoma, treatment options are minimal. Accordingly, there is a need to study new therapeutic methods for the treatment of this disease. In this situation, high hopes were placed on targeted therapy, in particular, the family of epidermal growth factor receptors, c-Kit are the most frequently studied molecular targets. Due to the rare occurrence of adenoid cystic carcinoma, the number of cases of using targeted therapy for analysis is relatively small, so each clinical observation is of particular value. The following is a clinical case of treatment of recurrent adenoid cystic carcinoma using a personalized treatment approach.Aim. To describe the clinical observation of the use of targeted drugs in recurrent or metastatic adenocystic cancer of the salivary glands.